A symbol of infinite (be)longing: Psychosocial rhythms of inclusion and exclusion at South African universities - Liccardo, S. (South African Journal of Higher Education, 2018)
This paper argues that the life histories of Black South African women scientists provide a telling story of psychosocial (trans)formation because they experience the world as outliers; paradoxically positioned within an interstitial ‘zone of (non)being’ between their dual sense of inclusion in and exclusion from marginal and dominant groups. Using a narrative method to enquire into the lives of fourteen scholarship students in Science, Technology, Engineering, and Mathematics (STEM) fields at a historically white South African university (HWU), this paper proposes an infinity model to illustrate how these young women locate their-selves in the field of higher education through recognition, dislocate their-selves from the field through misrecognition and infinitely recreate new subjectivities and epistemic communities at the intersecting space in between inclusion-exclusion.